HUBUNGAN EKSPEKTANSI TERHADAP DOSEN PEMBIMBING DENGAN MOTIVASI MENULIS SKRIPSI (Departement of Psychology, Faculty of Education, Universitas Negeri Semarang, 2012)
The research was conducted at the Department of Psychology UNNES. Research subjects numbered 50 people who are determined using the technique incidental. Ekspektansi Ekspektansi measured using a scale. Ekspektansi scale has a value of 0.950 reliability. The scale has 40 items Ekspektansi valid from the beginning item number 50 items. While the motivation to write Thesis measured using a scale of motivation. Motivation scale has a reliability value of 0.909. The scale has 40 items valid motivation. Correlation test using multiple regression analysis technique is done using SPSS 19.0 for windows. The results showed variable Ekspektansi on the subject of research is the category of being, which means that the student possessed ekspektansi mediocre. Motivational variables in the study subjects are at high criteria. The results showed that there is a positive relationship between ekspektansi with motivation to the value of r = 0.351 with a significance value or p = 0.012.